Pengaruh Injeksi Semen Pada Lereng Tanah Berpasir Terhadap Permeabilitas Tanah - I Wayan Arya; I Wayan Intara; I Nyoman Ramia; I Wayan Wiraga; I G A G Suryanegara (Politeknik Negeri Semarang, 2019)
Natural slope that are formed from the soil often experience landslides. Landslide occurs because the driving force received by the slope is greater than the ability of the slope to resist it. Thus forming a sliding plane that has a low stability. Factors that decrease the stability of the slope are infiltration of rainwater, vibrations that may come from earthquakes or moving loads, construction loads, and cracks. Rainwater that infiltrate through slope causes active force on the slopes and also decreases soil strength. Landslides due to infiltration of rainfall are common problems on residual soil slopes from the tropical region. Soil stabilization process for soil that have been experienced prior landslide, often encounter difficulty in compacting soil to form slope bodies. Loose sandy soil slopes has a very low strength so that expensive construction is needed. One possible way to do this is to fill the pores of the soil with certain aggregates. One of the aggregates is cement. The cement material is chosen because cement when liquid can seep in and fill the pores of the soil. After drying this cement can increase soil permeability and reduce soil pore numbers. Filling cement into the soil pores can be done by injection of liquid cement. The problems that will be raised in this study are: What is the change in soil permeability rate if the soil is injected with cement and how much changes in soil pore size when injected with cement. The method used in this study is to make a test model in the laboratory. By comparing soil without cement injection with soil that has been injected with cement, it will be known to increase soil permeability and decrease the soil pore number. From the preliminary test with proctor test, the maximum density was 1,286 gram/cm3 and the optimum water content was 18%. Decrease of coefisien permeability from without cement injection to with cement injection 31,5 %.